Introduction of DNA-based Methods to Agriculture Through Molecular Taxonomic Examination of Poa Species - Zubor, Ákos; K. Szabó, Zsuzsa; Nyakas, Antónia; Papp, Mária; Prokisch, József (Acta Agraria Debreceniensis, 2005)
biological methods, one among them is AFLP that is well applicable for taxonomic research. Bluegrass species, that are important components of meadow associations, thus their thorough knowledge is necessary in maintaining biodiversity, were examined with bringing this method to perfection.Taxonomic relationship of the members of Poa pratensis aggregation is a controversial issue. Present study aimes to identify the members of this group, with a developed AFLP method through molecular taxonomic examination of Poa species in meadows nearby Debrecen, revealing their genetical distances. Species of the aggregation show a great genetic variability, but their genetic proximity approves the use of the term aggregation. Results established wider geographical investigation of three species of the aggregation. The distinctness of the species based on their morphological features was confirmed according to their genetical basis as well. The method overall turned out to be appropriate for the taxonomic research of bluegrass species like Poa pratensis and its aggregation.